EFFECT OF ORGANIC FERTILIZERS AND MAGNETIZED WATER IN GROWTH AND YIELD OF MEDICAL PUMPKIN FROM FIXED OIL AND ITS COMPONENTS - & et al., Almrani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A field experiment was carried out at the Experimental Field of Hort. Dept/ College of Agric .Abu-Ghraib/University of Baghdad during the spring growth season and autumn of 2013, to study effect organic fertilizer and magnetized water on Growth and production of medicinal pumpkin from fixed oil and its components, the experiment included two factors, First was irrigation with normal water(A1), irrigation with magnetized water 500 gauss(A2) and the second factor included six levels of fertilizers are: control (without fertilization) (F1), chemical fertilization (Recommended) (F2) ,fertilization with mushrooms waste 5%(F3), 7.5% (F4), fertilization with poultry manure 5% (F5), 7.5% (F6). The experiment was implemented within Nested design and three replications for spring season (open field) and autumn season (green house). The results showed that the significant increase in plant height at treatments F6 and F4 with A2 in the open field and with A1 in green house (365.1, 312.3, 597.9, 504.9 cm respectively). Reached highest number of branches and dry weight at treatment F6 with A2, leaf area with A1 of open field, (3.2 branch .plant-1 , 113 dsm2 152.1 g respectively) and the highest increase in the leaf area and dry weight at treatment F4 with A1 of green house (498.5 dsm2 , 273.5 g respectively). Highest yield of the fruits was at treatment F2 with A1 and F6 with A2 in open field(40.0, 33.5 ton .h-1 respectively) and treatment F5 with A1in green house (29.7 ton .h-1). Happened highest yield of seeds at treatment F6 and F4 with A1 in open field(240.4, 231.8 kg .h-1 respectively) and at treatment F2 with A1 in green house (401.2 kg .h-1) also a higher yield of oil at F4 and F6 with A1 in open field(58.1, 55.8 kg.h-1 respectively) and at treatments F5, F4 with A1 in green house (142.1, 139.7 kg.h-1 respectively) Reached highest percentage of oleic acid at F1 with A2 in green house (17.0%) while reached higher percentage of linoleic acid at treatment F4 , F2 with A1 (68.3, 68.1% respectively) and the higher percentage of phytosterols at treatments F3 with A2 in open field (1.9%) and the treatment of F1 with A2 in green house (2.3%).